Poland daily - Mazierska, Ewa (Berghahn Books, 2017)
Like many Eastern European countries, Poland has seen a succession of divergent economic and political regimes over the last century, from prewar
Literaturverzeichnis Seite 309-328
Keywords: Film; Gesellschaft; Alltag; Wirtschaft; Arbeit; Verbrauch; Soziale Schichtung; Kino